2016
DOI: 10.1097/mnm.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and microbiodistribution of 64Cu-labeled collagen-binding peptides in chronic myocardial infarction

Abstract: Objectives To evaluate the pharmacokinetics and microbiodistribution of 64Cu-labeled collagen binding peptides. Method The affinity constant (KD), association (ka) and dissociation rate constant (kd) for the peptide collagelin or its analogue (named CRPA) binding to collagen were measured by bio-layer interferometric analysis. Rats (n = 4–5) with myocardial infarction or normal were injected IV with the 64Cu-labeled peptides or 64Cu-DOTA as a control. Dynamic PET imaging was performed for 60 min at 7- to 8-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Surface Plasmon Resonance binding studies of the unconjugated and unlabeled LRELHLNNN peptide demonstrated sub-micromolar affinity (K d = 170 nM) to collagen type I. This is an improvement as compared to [ 68 Ga]Ga-CBP8 (2.1 µM) [9] [10,48,49] and collagelin (1.5-2 µM) [15][16][17]47,79], but direct comparison should be taken with caution, as different assays were used for affinity assessment for the different tracers. The binding of radiolabeled peptide correlated with the fibrosis grade in liver biopsies, as assessed by Sirius Red staining of collagen.…”
Section: Targets and Radioligands To Detect The Fibrotic Scarmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface Plasmon Resonance binding studies of the unconjugated and unlabeled LRELHLNNN peptide demonstrated sub-micromolar affinity (K d = 170 nM) to collagen type I. This is an improvement as compared to [ 68 Ga]Ga-CBP8 (2.1 µM) [9] [10,48,49] and collagelin (1.5-2 µM) [15][16][17]47,79], but direct comparison should be taken with caution, as different assays were used for affinity assessment for the different tracers. The binding of radiolabeled peptide correlated with the fibrosis grade in liver biopsies, as assessed by Sirius Red staining of collagen.…”
Section: Targets and Radioligands To Detect The Fibrotic Scarmentioning
confidence: 99%
“…However, somewhat higher uptake and longer retention in the kidney and small intestine was observed for the 18 F-labeled counterpart. The faster clearance of the 68 Ga-labeled counterpart from the kidney presents a considerable advantage in terms of the possibility to image collagen type I in kidney, which might not be possible with the 18F-labeled counterpart [19] or CBP8 [10,48,49] and collagelin analogues [15][16][17]47,79]. However, the agent showed low in vivo stability in rodents, with only 10-15% of the intact fraction after 60 min.…”
Section: Targets and Radioligands To Detect The Fibrotic Scarmentioning
confidence: 99%
“…In cardiac models, SPECT and PET probes based on a peptide known as collagelin accumulate in areas of myocardial infarction (Fig. 2.4) [33, 47]. In lung and liver models, other peptide-based probes accumulate in fibrotic tissue ([14, 78], p. 201).…”
Section: Organ-scale Imagingmentioning
confidence: 99%
“…This figure depicts positron-emission tomography images taken at several time points after probe injection. The top row shows a probe based on the collagelin analogue CRPA, and the bottom a probe based on collagelin [33]. (Figure Permission granted through RightsLink)…”
Section: Fig 21mentioning
confidence: 99%